Analisis Penilaian Kinerja Karyawan Berdasarkan Kpi Metode Balanced Scorecard Di Pegadaian Syariah ‘X’ Kota Surabaya - Nur Aini Agustina; Muchtolifah Muchtolifah; Putra Perdana (Universitas Mataram, 2023)
The purpose of this test is to understand and describe employee performance appraisal using the Key Exhibition Marker with the Decent Scorecard approach at Pegadaian Syariah 'X' Surabaya. Describes checks and assessments in evaluating representative implementations using KPIs with the Decent Scorecard Approach. This study uses qualitative methods and descriptive analysis. The selection of research subjects was carried out purposively. Data collection methods include: documentation, interviews, and observation. Inductive approach to data analysis departs from empirical facts before investigating and evaluating the results. The validity of the information used is source triangulation. Based on the research findings, Pegadaian Syariah uses a Balanced Scorecard framework with four perspectives for evaluating employee performance. Customer perspective, internal business process perspective, financial perspective, and learning and development perspective. From a financial perspective, the target rating weight is 60%; from the customer's perspective, the target weight is 15%; from the perspective of internal business processes, the target weight is 15%; and from a learning and growth perspective, the target weight is 10%. From the beginning of the year to the end of the year, employee performance is assessed from the highest to the lowest position